Strategi Guru Paud Dalam Membangun Karakter Religius Anak Melalui Pembiasaan Duha Di Tk Nurul Huda - Siti Nuraisyah, Neli; Sianturi, Risbon; Gardana, Gilar (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Building a child's character formation requires habituation. To create good habits, habits must be carried out regularly in everyday life. As a result, instilling religious and moral principles in early childhood is very important. The aim of this research is to study in depth how PAUD teachers help children become more religious by teaching them habits such as the duha prayer. Data was collected using descriptive qualitative methods through documentation, in-depth interviews and observations with speakers consisting of school principals and teaching staff there. For the results of the analysis, researchers combine data collection findings from reliable sources with data collection findings that are converted into text. The results show that there are differences between children who are used to performing Dhuha prayers and children who are not. The aim of this habituation is to make children accustomed to positive things, understand religion better, and have good morals. It is recommended that this habituation be carried out regularly and involve the role of parents so that the results are better